S’unir au Prophète. L’expérience matérielle, esthétique et dévotionnelle du Dalā’il al-Khayrāt au Maroc. Approches codicologique et anthropologique - Hiba Abid; Anouk Cohen (L’Année du Maghreb)
The Dalā’il al-Khayrāt wa Shawāriq al-anwār fī dhikr al-ṣalāt ‘alā al-Nabiy al-mukhṭār (Dalā’il al-Khayrāt) is a book of prayers and invocations about the Prophet Muhammad, written around 857/1453 by the Moroccan mystic Muḥammad b. Sulaymān al-Jazūlī (d. 869/1465), founder of a new Sufi path, the Jazūliyya, considered as a branch of the Shādhiliyya, and whose popularity very quickly won over the entire kingdom. The figure of al-Jazūlī emerged in a context marked by deep political, social and religious agitation in Morocco, the causes of which go back to the beginning of the 9th/15th century. Al-Jazūlī bases his legitimacy on two concepts: on the one hand, his spiritual lineage (cherifism) through his genealogy, which he traces back to the Prophet, and, on the other hand, his spiritual saintliness (silsila), the chain of martyrs who initiated him into the mystical tradition, themselves the descendants of the Prophet. The Dalā’il al-Khayrāt is part of a well-known tradition of devotional literature in Morocco, available in various genres devoted to the Prophet, such as poetry or collections of prayers and invocations.In these texts, drawn essentially from the Hadiths, prayer for the Prophet is presented as the means par excellence for the one praying to invoke the presence of Muhammad, and to benefit from his power of protection and, above all, his function of intercession on the day of the Last Judgement. This is why the Dalā’il quickly became one of the most popular devotional books in the Sunni Muslim world, and particularly in Morocco. This success is not foreign to the exhortation of al-Jazūlī, to the recitation of prayers for the “Messenger of God”, which would be, according to him, the “road that leads to God”. At the same time, the material and aesthetic forms of the manuscripts of the Dalā’il were progressively adapted to frequent uses. The miniaturisation of manuscripts allows them to be recited at any moment of the day or week and in all situations. Their abundant illumination aims to facilitate the memorisation of the prayers while accompanying each division of the text. For believers, the book object was a privileged medium for uniting with the Prophet.Today, the Dalā’il continues to be the subject of great fervour in the Muslim world, in particular in the Maghreb. In Morocco, where the survey was conducted, we find examples of printed books in the bookshops and “roadworks” of the large cities. The text circulates above all in the zawiyas, where the prayers of the Dalā’il are collectively recited once a week. Just like the manuscripts produced in the past, many formats of the printed book are available to the reader – large, medium or miniature – thus adapting to their uses and needs. Aside from printed books, readers of the Dalā’il may choose, or prefer, the digital version of the text, via applications downloaded to mobile phone. This kind of medium led us to explore how the physical changes of the book went hand in hand with a modification of the relationships of the faithful to the text of the Dalā’il, to its transmission and, more broadly, to their way of uniting with the Prophet. To bring this study to a successful conclusion, we examined the present practices and representations of the book of the Dalā’il, little explored to date. To this end, the article draws on codicological and anthropological approaches to the book to examine how the materiality of the object informs the cultural practices that are attached to it, and the material and aesthetic experience that it supports, in order to unite with the Prophet, and also reconfigures these.